2015
DOI: 10.1021/acscatal.5b00347
|View full text |Cite
|
Sign up to set email alerts
|

Unintuitive Inverse Dependence of the Apparent Turnover Frequency on Precatalyst Concentration: A Quantitative Explanation in the Case of Ziegler-Type Nanoparticle Catalysts Made from [(1,5-COD)Ir(μ-O2C8H15)]2 and AlEt3

Abstract: A 1 H NMR spectrum of the precursor was obtained via an Inova 400 MHz NMR instrument.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
4
17
0
1
Order By: Relevance
“…Some researchers tend to use the number of surface atoms or amount of cocatalysts to calculate the TOF, namely the apparent TOF. Considering the fact that the number of active sites may not be proportional to the surface atoms, the apparent TOF should be much lower than the real TOF . For example, only edge atoms are active for redox reactions on some catalysts .…”
Section: Fundamentals In Photocatalysismentioning
confidence: 99%
“…Some researchers tend to use the number of surface atoms or amount of cocatalysts to calculate the TOF, namely the apparent TOF. Considering the fact that the number of active sites may not be proportional to the surface atoms, the apparent TOF should be much lower than the real TOF . For example, only edge atoms are active for redox reactions on some catalysts .…”
Section: Fundamentals In Photocatalysismentioning
confidence: 99%
“…Recently, Finke and co-workers have analyzed similar counterintuitive behavior in hydrogenations with Ziegler-type nanoparticle catalysts prepared from Ir precatalysts (30). Likewise, benzene borylation has been described with Ir nanoparticles at 80°C with activities that are considerably lower than those for homogeneous catalysts (31).…”
mentioning
confidence: 99%
“…Previous reports detailingachanging TOF relatedt he effect to association/dissociationo fc atalyst, supportedb yk inetic data. [47] We hypothesize that catalyst order is continually decreasing with increasing concentration of 1a;V TNA was conducted above andb elow 100 mm to highlight the difference in order. Am onomeric POSS-triol is proposed to be the active catalyst, suggesting the variable order in 1a is related to an off-cycle event that is more significant at higher concentrations.…”
Section: Resultsmentioning
confidence: 97%
“…Apparent turnover frequencies (TOF app = k obs /[ 1 a ]) vs. [ 1 a ]) were calculated, and it was observed that TOF app plateaus at catalyst concentrations >100 m m (see the Supporting Information). Previous reports detailing a changing TOF related the effect to association/dissociation of catalyst, supported by kinetic data …”
Section: Resultsmentioning
confidence: 99%